The role of islamic social finance in supporting fair fiscal policies: A study of ZISWAF integration in Indonesia - Khoirudin Khoirudin; Nanda Suryadi; Raja Sakti Putra Harahap (Nur Science Institute, 2025)
This study aims to analyze the role of Islamic Social Finance (ISF), particularly zakat, infaq, sadaqah, and waqf (ZISWAF), in supporting equitable fiscal policies in Indonesia. Using a descriptive-analytical qualitative approach, this study examines the potential, challenges, and models for integrating Islamic social finance instruments and state fiscal policies. The results show that ZISWAF has great potential as an alternative source of social financing, with the potential value of national zakat reaching IDR 327 trillion per year, but only about 4% has been realized. The integration of ZISWAF into the fiscal system plays a role in strengthening wealth redistribution, expanding the state's fiscal space, and supporting the achievement of Sustainable Development Goals (SDGs) without increasing the tax burden on the community. However, this study also identifies various obstacles, such as weak institutional coordination, overlapping regulations, and low public literacy regarding Islamic social finance. Digital transformation through Islamic fintech has the potential to be a solution by increasing the transparency, efficiency, and accountability of ZISWAF management. This study concludes that the integration of ZISWAF into fiscal policy supported by digital governance and the principles of maqasid al-shariah is a strategic step towards fiscal justice and sustainable social welfare in Indonesia.